2018
DOI: 10.1111/ffe.12923
|View full text |Cite
|
Sign up to set email alerts
|

Multiple interfacial cracks in dissimilar piezoelectric layers under time harmonic loadings

Abstract: In this study, the dislocation‐based model is developed to study the interaction between time‐harmonic elastic waves and multiple interface cracks in 2 bonded dissimilar piezoelectric layers. In this model, cracks are represented by a distribution of so‐called electro‐elastic dislocations whose density is to be determined by satisfying the boundary conditions. Using the Fourier transform, this formulation leads to 2 singular integral equations, which can be solved numerically for the densities of electro‐elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Lastly, Ayatollahi et al [36] examined the presence of multiple interfacial cracks across distinct piezoelectric layers subjected to time-harmonic loadings. Observations of straight and sharp cracks have been documented in silicon 100 [37].…”
Section: -Introductionmentioning
confidence: 99%
“…Lastly, Ayatollahi et al [36] examined the presence of multiple interfacial cracks across distinct piezoelectric layers subjected to time-harmonic loadings. Observations of straight and sharp cracks have been documented in silicon 100 [37].…”
Section: -Introductionmentioning
confidence: 99%
“…Liu et al (2013) implemented an extended finite element method (XFEM) to study the behaviour of dynamic cracks of functionally graded piezoelectric materials under impact loading. The analysis of interface cracks in bi-material piezoelectric ceramics and laminates deals with the effect of the polarization on the interfacial interaction of the frac-ture (Govorukha et al 2016, Li and Chen 2007, Tian et al 2015, Nourazar and Ayatollahi 2016, Zhou et al 2019, Viun et al 2018, Ayatollahi and Fartash 2019, Yu et al 2015. Tian et al (2015) reported the effect of in-plane electrical loading on the periodically distributed interfacial cracks in multilayered piezoelectric composites.…”
Section: Introductionmentioning
confidence: 99%
“…Nourazar and Ayatollahi (2016) have studied the dynamic problem of multiple moving cracks at the interface of the piezoelectric ceramics for an outof-plane mechanical loading and an in-plane electrical loading. Ayatollahi and Fartash (2019) discussed a dislocation based model that discuss the interaction of interfacial cracks under the influence of time harmonic elastic waves.…”
Section: Introductionmentioning
confidence: 99%